Scattering of a flat top solitons of cubic - quintic nonlinear Shrodinger equation by delta potential - Umarov, Bakhram A.; Busul Aklan, Nor Amirah (2016)
The flat top soliton is a localized solution of cubic - quintic Nonlinear Shrodinger equation (C-Q NLSE) that can propagate preserving its shape. In this work we consider the interaction of soliton with weak external localized potentials. It is shown that depending on an initial velocity the soliton may be re ected or transmitted by potential. The approximate analytical results based on varational approach qualitatively confirmed by numerical simulations.